Peran Hukum Adat Dalam Penyelesaian Sengketa Masyarakat Lokal - Sopalatu, Abd Raid; Lailita, Rizki Ananda Agust; Sudja’i, A (PATTIMURA Law Study Review, 2025)
Customary law plays a significant role in Indonesian society as a dispute resolution mechanism that emphasizes the values of togetherness, kinship, and communal justice. Amid the challenges of modernization and agrarian conflicts, local communities tend to favor customary law over formal state law due to its greater social and cultural relevance. This study aims to analyze the role of customary law in resolving disputes within local communities by highlighting deliberation, mediation, and negotiation as the primary mechanisms. A qualitative approach was employed, based on literature review and case analysis of indigenous communities such as the Batak and Minangkabau. The findings show that customary law ensures peaceful and sustainable conflict resolution because it is rooted in local values such as mutual cooperation, sacrifice, and spirituality. Customary leaders play a key role as mediators, maintaining community stability and harmony. Despite the dominance of formal law, customary law remains relevant and adaptable in meeting community needs. This study underscores the importance of recognizing and integrating customary law into the national legal system to develop a more inclusive, contextual, and socially just approach to dispute resolution.